High Rate, Long Lifespan LiV3O8 Nanorods as a Cathode Material for Lithium‐Ion Batteries. Issue 18 (6th March 2017) - Chen, Zhongxue; Xu, Fei; Cao, Shunan; Li, Zhengfeng; Yang, Hanxi; Ai, Xinping; Cao, Yuliang
Abstract : LiV3 O8 nanorods with controlled size are successfully synthesized using a nonionic triblock surfactant Pluronic‐F127 as the structure directing agent. X‐ray diffraction, scanning electron microscopy, and transmission electron microscopy techniques are used to characterize the samples. It is observed that the nanorods with a length of 4–8 µm and diameter of 0.5–1.0 µm distribute uniformly. The resultant LiV3 O8 nanorods show much better performance as cathode materials in lithium‐ion batteries than normal LiV3 O8 nanoparticles, which is associated with the their unique micro–nano‐like structure that can not only facilitate fast lithium ion transport, but also withstand erosion from electrolytes. The high discharge capacity (292.0 mAh g −1 at 100 mA g −1 ), high rate capability (138.4 mAh g −1 at 6.4 A g −1 ), and long lifespan (capacity retention of 80.5% after 500 cycles) suggest the potential use of LiV3 O8 nanorods as alternative cathode materials for high‐power and long‐life lithium ion batteries. In particular, the synthetic strategy may open new routes toward the facile fabrication of nanostructured vanadium‐based compounds for energy storage applications. Abstract : LiV3 O8 nanorods with controlled size with a high discharge capacity of 275.8 mAh g −1 and excellent capacity retention of 80.5% after 500 cycles at 1 C are demonstrated. They also exhibit a high rate capability up to ≈21 C, possibly serving as alternative cathode materials for high‐power and long‐life lithium ion batteries.